Takotsubo Cardiomyopathy in Traumatic Brain Injury: A Case Report (Bangladesh Critical Care Journal, 2017)
Background: Takotsubo cardiomyopathy (TC) is a well-known complication of severe brain insult but has been rarely described in patients with traumatic brain injury (TBI).Methods: Case report and review of literature.Results: We report a 25-year-old lady with moderate traumatic brain injury (TBI) developing circulatory shock. Takotsubo cardiomyopathy (TC) was diagnosed by repeated echocardiography. Cardiovascular support by pressor agents led to hemodynamic stabilization after initiation of noradrenaline. Cardiac function fully recovered within 2 weeks. We performed an in-depth literature review and identified 17 reported patients with TBI and TC. Clinical course and characteristics are discussed in the context of our patient.Conclusion: TC is rarely diagnosed after TBI and may lead to poor outcome if not addressed in time.Bangladesh Crit Care J September 2017; 5(2): 143-146